Is voluntary certification of tropical agricultural commodities achieving sustainability goals for small-scale producers? A review of the evidence - DeFries, Ruth S.; Fanzo, J.; Mondal, P.; Remans, R.; Wood, S.A. (IOP Publishing, 2017)
Over the last several decades, voluntary certification programs have become a key approach to promote sustainable supply chains for agricultural commodities. These programs provide premiums and other benefits to producers for adhering to environmental and labor practices established by the certifying entities. Following the principles of Cochrane Reviews used in health sciences, we assess evidence to evaluate whether voluntary certification of tropical agricultural commodities (bananas, cocoa, coffee, oil palm, and tea) has achieved environmental benefits and improved economic and social outcomes for small-scale producers at the level of the farm household. We reviewed over 2600 papers in the peer-review literature and identified 24 cases of unique combinations of study area, certification program, and commodity in 16 papers that rigorously analyzed differences between treatment (certified households) and control groups (uncertified households) for a wide range of response variables. Based on analysis of 347 response variables reported in these papers, we conclude that certification is associated on average with positive outcomes for 34% of response variables, no significant difference for 58% of variables, and negative outcomes for 8% of variables. No significant differences were observed for different categories of responses (environmental, economic and social) or for different commodities (banana, coffee and tea), except negative outcomes were significantly less for environmental than other outcome categories (p = 0.01). Most cases (20 out of 24) investigated coffee certification and response variables were inconsistent across cases, indicating the paucity of studies to conduct a conclusive meta-analysis. The somewhat positive results indicate that voluntary certification programs can sometimes play a role in meeting sustainable development goals and do not support the view that such programs are merely greenwashing. However, results also indicate that certification is not a panacea to improve social outcomes or overall incomes of smallholder farmers. Rigorous analysis, standardized criteria, and independent evaluation are needed to assess effectiveness of certification programs in the future.